2018
DOI: 10.1159/000493497
|View full text |Cite
|
Sign up to set email alerts
|

Repression of PDK1- and LncRNA HOTAIR-Mediated EZH2 Gene Expression Contributes to the Enhancement of Atractylenolide 1 and Erlotinib in the Inhibition of Human Lung Cancer Cells

Abstract: Background/Aims: We previously showed that the major bioactive compound of Atractylodes macrocephula Koidz atractylenolide 1 (ATL-1) inhibited human lung cancer cell growth by suppressing the gene expression of 3-Phosphoinositide dependent protein kinase-1 (PDK1 or PDPK1). However, the potentially associated molecules and downstream effectors of PDK1 underlying this inhibition, particularly the mechanism for enhancing the anti-tumor effects of epidermal growth factor receptor-tyrosine-kinase inhibitors (EGFR-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…HOTAIR is well-known to influence chromatin compactness by serving as a molecular scaffold for PRC2, thereby recruiting and affecting PRC2 occupancy on genes genome-wide (95, 96). Importantly, HOTAIR overexpression has been reported in several solid tumors and hematological malignancies, including AML and diffuse large B cell lymphoma, and has been positively correlated with initiation, progression, drug resistance, and poor prognosis (9599). In MM, however, no aberrant expression of HOTAIR in MM cells so far has been reported (100).…”
Section: Histone Methylation Enzymes and Multiple Myelomamentioning
confidence: 99%
“…HOTAIR is well-known to influence chromatin compactness by serving as a molecular scaffold for PRC2, thereby recruiting and affecting PRC2 occupancy on genes genome-wide (95, 96). Importantly, HOTAIR overexpression has been reported in several solid tumors and hematological malignancies, including AML and diffuse large B cell lymphoma, and has been positively correlated with initiation, progression, drug resistance, and poor prognosis (9599). In MM, however, no aberrant expression of HOTAIR in MM cells so far has been reported (100).…”
Section: Histone Methylation Enzymes and Multiple Myelomamentioning
confidence: 99%
“…Pharmacokinetic studies in rats have demonstrated that, after oral administration, AT-I is readily absorbed and persists for extended periods of time, suggesting good oral bioavailability (Wang et al, 2008). AT-I has a wide range of biological and pharmacological properties, including neuroprotective, antiallergic, anti-inflammatory, and anti-cancer activities (Wang et al, 2009;Lim et al, 2012;More and Choi, 2017;Xiao et al, 2018). Previous studies have shown that AT-I is beneficial in treating various cancers through the regulation of different molecules and pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we demonstrated the utility of ATL‐1 for this purpose. Research has shown the unique therapeutic potential of ATLs against cancers such as melanoma, 39 lung cancer, 40 and ovarian cancer 41 . In particular, Zhang et al revealed that ATL‐II, another member of the ATL family with similar structural characteristics as ATL‐1, improved the chemotherapeutic efficacy against CRC by suppressing the viability and proliferation of CRC cells.…”
Section: Discussionmentioning
confidence: 99%